2010
DOI: 10.4269/ajtmh.2010.09-0644
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Asymptomatic Cryptosporidium Infections in Children in a Semi-Urban Slum Community in Southern India

Abstract: Cryptosporidium is a leading cause of childhood diarrhea in developing countries. We investigated symptomatic and asymptomatic cryptosporidiosis in 20 children less than two years of age in a semi-urban slum in southern India. All surveillance (conducted every two weeks) and diarrheal samples from 20 children (n = 1,036) with cryptosporidial diarrhea previously identified by stool microscopy were tested by polymerase chain reaction–restriction fragment length polymorphism for species and subgenotype determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…Previous studies have shown that Cryptosporidium is an important cause of gastroenteritis in children in developing countries (45)(46)(47); in the recent GEMS, around 10% of diarrhea cases in children younger than 2 years were attributed to Cryptosporidium (3). In our study, Cryptosporidium was detected in 30% of children with diarrhea versus 11% of asymptomatic children, and 25% of patients had Cryptosporidium detected with C T values below the cutoff of 35, indicating a causative role.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Cryptosporidium is an important cause of gastroenteritis in children in developing countries (45)(46)(47); in the recent GEMS, around 10% of diarrhea cases in children younger than 2 years were attributed to Cryptosporidium (3). In our study, Cryptosporidium was detected in 30% of children with diarrhea versus 11% of asymptomatic children, and 25% of patients had Cryptosporidium detected with C T values below the cutoff of 35, indicating a causative role.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the same community have shown a high burden of childhood cryptosporidiosis. 31,32 …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we investigated the clinical features and molecular and spatial epidemiology of cryptosporidiosis in a birth cohort of children in a semiurban slum community in South India (2,3). The most common species identified in diarrheal stool samples from these children was C. hominis, with gp40/15 subtype Ia predominating.…”
mentioning
confidence: 99%